The Impact of Implementing Technology Brand Reputation and University External Image on The Student Adoption to Change: A Moderated Mediation Approach - Anwar, Farooq; Awan, Nosheen Pervaiz; Arshad, Muhammad (International Journal of Membrane Science and Technology, 2023)
Objective- The basic aim or objective of this study is to investigate the impact of implementing technology brand reputation and the university's external image on the student’s adoption to change. Based on the social identity theory this research recommends that implementing technology with brand reputation and university external image may induce their students to adopt these technologies. It is further argued that the effect of these factors also depend on the student’s university identification and their culture. Methodology/ design/approach - This study used the convenience sampling method for collecting the data from the 370 students of the educational sector in Pakistan during the implementation of new online technology systems. The model of this study was tested by using the structure equation modeling technique in Amos. Findings- The analysis of this study suggests that implementing technology brand reputation and the university external image positively increased the student’s adoption to change and their relationship is also importance for the better performance of university when student’s deification with the university are high and when they are loyal to their institution then they easily adopt the changes whatever technology is being implement in their institution. Value/originality - In this latest ere of research, technology play an important role in educational sector for different activities or most popularly for online classes during an epidemic situation which is need to study the role of brand reputation and university image in the student identification and adoption behavior. The study fills this gap and has two main contributions: one is how reputation of technological brand which is implementing in the university and their external image play a role in student adoption for change perspectives and second is how social identity perspective model leads students to quickly adopt this technological change.